Run Code  | API  | Code Wall  | Misc  | Feedback  | Login  | Theme  | Privacy  | Patreon

## simult Q3 with latex code + Quad factorization

 Language:Ada Assembly Bash C# C++ (gcc) C++ (clang) C++ (vc++) C (gcc) C (clang) C (vc) Client Side Clojure Common Lisp D Elixir Erlang F# Fortran Go Haskell Java Javascript Kotlin Lua MySql Node.js Ocaml Octave Objective-C Oracle Pascal Perl Php PostgreSQL Prolog Python Python 3 R Rust Ruby Scala Scheme Sql Server Swift Tcl Visual Basic Layout:Vertical Horizontal
 Show compiler warnings [ + ] Show input Compilation time: 1.02 sec, absolute running time: 0.68 sec, cpu time: 0.42 sec, memory peak: 41 Mb, absolute service time: 1,82 sec
 edit mode |  history  | discussion
(-2x + 7)(6x + 7) = -12x^2+28x+49, x = 7/2, -7/6
(-7x + 5)(1x + 2) = -7x^2-9x+10, x = 5/7, -2
(1x + 7)(5x + 3) = 5x^2+38x+21, x = -7, -3/5
(5x + 8)(1x - 5) = 5x^2-17x+40, x = -8/5, 5
(1x - 5)(1 - 3x) = -3x^2+16x-5, x = 5, 1/3
(6x - 5)(1 - 6x) = -36x^2+36x-5, x = 5/6, 1/6
(2x + 7)(6x + 1) = 12x^2+44x+7, x = -7/2, -1/6
(5x + 2)(1x + 5) = 5x^2+27x+10, x = -2/5, -5
(8x + 3)(4x - 7) = 32x^2-44x+21, x = -3/8, 7/4
(-5x + 1)(-2x + 1) = 10x^2-7x+1, x = 1/5, 1/2
(-8x + 1)(5x + 3) = -40x^2-19x+3, x = 1/8, -3/5
(4x - 3)(5x - 2) = 20x^2-23x+6, x = 3/4, 2/5
(-4x + 1)(2x + 7) = -8x^2-26x+7, x = 1/4, -7/2
(-3x + 1)(-7x + 5) = 21x^2-22x+5, x = 1/3, 5/7
(6x + 7)(4x + 7) = 24x^2+70x+49, x = -7/6, -7/4
(-7x + 5)(4x + 5) = -28x^2-15x+25, x = 5/7, -5/4
(1x - 3)(1x - 7) = 1x^2-10x+21, x = 3, 7
(6x + 1)(6x + 1) = 36x^2+12x+1, x = -1/6, -1/6
(1x + 1)(1 - 5x) = -5x^2-4x+1, x = -1, 1/5
(7x + 5)(3x - 5) = 21x^2-20x+25, x = -5/7, 5/3
(3x - 5)(5 - 4x) = -12x^2+35x-25, x = 5/3, 5/4
(4x + 5)(2x + 1) = 8x^2+14x+5, x = -5/4, -1/2
(3x + 8)(6x + 1) = 18x^2+51x+8, x = -8/3, -1/6
(-7x + 5)(1x + 4) = -7x^2-23x+20, x = 5/7, -4
(1x - 7)(1 - 8x) = -8x^2+57x-7, x = 7, 1/8
(5x + 8)(7x - 6) = 35x^2+26x+48, x = -8/5, 6/7
(7x + 4)(1x + 8) = 7x^2+60x+32, x = -4/7, -8
(3x - 8)(7x - 6) = 21x^2-74x+48, x = 8/3, 6/7
(5x + 2)(-5x + 8) = -25x^2+30x+16, x = -2/5, 8/5
(1x + 1)(5x + 2) = 5x^2+7x+2, x = -1, -2/5
(-7x + 4)(5x - 7) = -35x^2+69x-28, x = 4/7, 7/5
(7x + 3)(7x - 6) = 49x^2-21x+18, x = -3/7, 6/7
(3x + 4)(1x - 7) = 3x^2-17x+28, x = -4/3, 7
(7x - 2)(6x + 5) = 42x^2+23x-10, x = 2/7, -5/6
(8x - 7)(5x + 2) = 40x^2-19x-14, x = 7/8, -2/5
(1x + 1)(7x + 1) = 7x^2+8x+1, x = -1, -1/7
(8x + 7)(1 - 3x) = -24x^2-13x+7, x = -7/8, 1/3
(-4x + 5)(4x + 7) = -16x^2-8x+35, x = 5/4, -7/4
(-5x + 1)(1x + 6) = -5x^2-29x+6, x = 1/5, -6
(-2x + 3)(1x + 4) = -2x^2-5x+12, x = 3/2, -4
(8x + 1)(7x + 8) = 56x^2+71x+8, x = -1/8, -8/7
(5x - 4)(1x + 6) = 5x^2+26x-24, x = 4/5, -6
(8x + 3)(-5x + 6) = -40x^2+33x+18, x = -3/8, 6/5
(-2x + 5)(1x + 4) = -2x^2-3x+20, x = 5/2, -4
(5x - 4)(7x - 6) = 35x^2-58x+24, x = 4/5, 6/7
(7x + 6)(2x + 3) = 14x^2+33x+18, x = -6/7, -3/2
(8x - 7)(5x + 6) = 40x^2+13x-42, x = 7/8, -6/5
(4x + 1)(2x + 1) = 8x^2+6x+1, x = -1/4, -1/2
(5x + 4)(-3x + 7) = -15x^2+23x+28, x = -4/5, 7/3
(6x + 7)(5 - 7x) = -42x^2-19x+35, x = -7/6, 5/7
(3x - 2)(1x + 8) = 3x^2+22x-16, x = 2/3, -8
(-7x + 8)(1x - 4) = -7x^2+36x-32, x = 8/7, 4
(-2x + 1)(1x - 6) = -2x^2+13x-6, x = 1/2, 6
(7x + 2)(8x + 7) = 56x^2+65x+14, x = -2/7, -7/8
(6x + 7)(4x + 7) = 24x^2+70x+49, x = -7/6, -7/4
(7x + 3)(8x - 7) = 56x^2-25x+21, x = -3/7, 7/8
(-2x + 1)(5x + 1) = -10x^2+3x+1, x = 1/2, -1/5
(7x + 8)(1 - 4x) = -28x^2-25x+8, x = -8/7, 1/4
(1x + 7)(8x + 7) = 8x^2+63x+49, x = -7, -7/8
(-1x + 1)(5x + 2) = -5x^2+3x+2, x = 1, -2/5
(-7x + 8)(3x + 7) = -21x^2-25x+56, x = 8/7, -7/3
(5x + 8)(8x - 7) = 40x^2+29x+56, x = -8/5, 7/8
(4x - 7)(3x + 8) = 12x^2+11x-56, x = 7/4, -8/3
(-2x + 3)(3x - 2) = -6x^2+13x-6, x = 3/2, 2/3
(2x + 7)(1 - 7x) = -14x^2-47x+7, x = -7/2, 1/7
(4x + 5)(-2x + 7) = -8x^2+18x+35, x = -5/4, 7/2
(8x + 5)(-7x + 8) = -56x^2+29x+40, x = -5/8, 8/7
(2x + 7)(7 - 6x) = -12x^2-28x+49, x = -7/2, 7/6
(1x + 8)(5x + 7) = 5x^2+47x+56, x = -8, -7/5
(3x - 5)(5x + 6) = 15x^2-7x-30, x = 5/3, -6/5
(5x - 2)(6 - 5x) = -25x^2+40x-12, x = 2/5, 6/5
(1x + 7)(3x - 5) = 3x^2+16x+35, x = -7, 5/3
(-7x + 4)(2x + 3) = -14x^2-13x+12, x = 4/7, -3/2
(3x + 5)(1 - 3x) = -9x^2-12x+5, x = -5/3, 1/3
(1x - 3)(8x - 7) = 8x^2-31x+21, x = 3, 7/8
(7x + 6)(5x + 6) = 35x^2+72x+36, x = -6/7, -6/5
(4x - 7)(7x - 6) = 28x^2-73x+42, x = 7/4, 6/7
(8x + 1)(-5x + 1) = -40x^2+3x+1, x = -1/8, 1/5
(3x - 8)(4 - 3x) = -9x^2+36x-32, x = 8/3, 4/3
(5x + 2)(8x + 5) = 40x^2+41x+10, x = -2/5, -5/8
(7x + 8)(1x - 2) = 7x^2-6x+16, x = -8/7, 2
(7x + 3)(4x + 7) = 28x^2+61x+21, x = -3/7, -7/4
(8x + 5)(8x + 5) = 64x^2+80x+25, x = -5/8, -5/8
(-5x + 6)(-2x + 3) = 10x^2-27x+18, x = 6/5, 3/2
(1x - 4)(7x - 3) = 7x^2-31x+12, x = 4, 3/7
(1x + 5)(7x - 3) = 7x^2+32x+15, x = -5, 3/7
(7x - 2)(2x + 7) = 14x^2+45x-14, x = 2/7, -7/2
(-8x + 1)(-7x + 1) = 56x^2-15x+1, x = 1/8, 1/7
(5x + 2)(-4x + 5) = -20x^2+17x+10, x = -2/5, 5/4
(2x + 7)(6x + 5) = 12x^2+52x+35, x = -7/2, -5/6
(4x + 3)(7x + 4) = 28x^2+37x+12, x = -3/4, -4/7
(7x - 6)(1x + 8) = 7x^2+50x-48, x = 6/7, -8
(4x + 1)(1x + 7) = 4x^2+29x+7, x = -1/4, -7
(-5x + 8)(6x + 1) = -30x^2+43x+8, x = 8/5, -1/6
(2x + 5)(5x - 4) = 10x^2+17x+20, x = -5/2, 4/5
(-3x + 7)(5x + 4) = -15x^2+23x+28, x = 7/3, -4/5
(1x + 3)(7 - 3x) = -3x^2-2x+21, x = -3, 7/3
(2x + 5)(1x - 4) = 2x^2-3x+20, x = -5/2, 4
(4x + 3)(1 - 7x) = -28x^2-17x+3, x = -3/4, 1/7
(5x - 2)(5x + 4) = 25x^2+10x-8, x = 2/5, -4/5